Methods and Cost Estimation for the Synthesis of Nanosized Lithium Sulfide. Issue 3 (2nd December 2020) - Yuan, Kai; Yuan, Lixia; Chen, Jie; Xiang, Jingwei; Liao, Yaqi; Li, Zhen; Huang, Yunhui
Abstract : Lithium sulfide (Li2 S) is an alternative cathode material for lithium‐sulfur batteries. It can mitigate the volume expansion problem encountered by the sulfur cathode, in addition, as a fully lithium‐inserted cathode, it can be paired with lithium‐free anodes or be assembled into anode‐free batteries. However, commercially available Li2 S powder delivers poor electrochemical performances due to the significant potential barrier during the first charging process, and therefore developing inexpensive synthesis route for nanosized Li2 S with small diameter and low charging overpotential becomes the key to the construction of practical Li2 S cathode. Herein, the preparation methods for Li2 S nanoparticles are summarized, including laboratory synthesis methods and potential large‐scale preparation routes; traditional industrial synthesis methods for commercially available Li2 S are also attached as references. In particular, the scalability of these methods is mentioned, and the costs of the resulted Li2 S products are also estimated and compared with the currently used cathode materials for Li‐ion batteries. In the end, the commercially worthwhile research pathways for Li2 S synthesis as well as the perspective on the practical production of Li2 S are discussed. Useful guidance for the selection of practical Li2 S synthesis routes is also provided. Abstract : The inexpensive synthesis of Li2 S particles with small diameter and low charging potential becomes the key to the construction of practical Li2 S cathodes. The preparation methods for Li2 S nanoparticles are summarized and evaluated in the terms of performance and cost.